2020
DOI: 10.2147/jir.s228361
|View full text |Cite
|
Sign up to set email alerts
|

<p>Modulation of Chronic Inflammation by Quercetin: The Beneficial Effects on Obesity</p>

Abstract: Obesity has become a major risk factor for the development of chronic diseases such as insulin resistance, type 2 diabetes mellitus, and cardiovascular disease. Moreover, obesity induces chronic inflammation in adipose tissue, liver, skeletal muscle, and the vascular system. Quercetin is the major representative of the flavonoid subclass of flavonols, which is ubiquitously contained within natural plants such as green tea, and vegetables, including onions and apples. Researchers have focused greater attention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(60 citation statements)
references
References 116 publications
3
56
0
1
Order By: Relevance
“…In fact, the increasing incidence of obesity and corresponding rise in type-2 diabetes are further challenging the prevention and treatment of CVD (253). The metabolic effects of quercetin against these two conditions have been equally encouraging and were recently reviewed elsewhere (254)(255)(256)(257)(258). In addition, it should be emphasized that, for clarity reasons, the effects of quercetin on the various biochemical and biomechanical signaling cascades involved in endothelial dysfunction were discussed as separate entities.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the increasing incidence of obesity and corresponding rise in type-2 diabetes are further challenging the prevention and treatment of CVD (253). The metabolic effects of quercetin against these two conditions have been equally encouraging and were recently reviewed elsewhere (254)(255)(256)(257)(258). In addition, it should be emphasized that, for clarity reasons, the effects of quercetin on the various biochemical and biomechanical signaling cascades involved in endothelial dysfunction were discussed as separate entities.…”
Section: Discussionmentioning
confidence: 99%
“…It has been mentioned in studies that quercetin has antioxidant, anti-inflammatory, antiviral, anti-obesity, antidepressant properties, as well as preventing cancer, diabetes, asthma, hypertension, and cardiovascular diseases [ 135 , 136 ]. A study reported by Ju et al [ 137 ] stated that quercetin decreases the abundance of E. coli and proteobacteria.…”
Section: Quercetinmentioning
confidence: 99%
“…An in vivo study conducted on 60 subjects showed a statistically significant reduction in IL-6 and C-reactive protein (CRP), after a supplementation of 500 mg/day of quercetin for 8 weeks [ 267 ]. Furthermore, quercetin seems to be able to reduce COX-2 [ 268 ] and inducible nitric oxide synthase (iNOS) gene expression [ 269 , 282 ]. Quercetin can improve the body’s antioxidant defenses by stimulating the synthesis of glutathione (GSH) and modulating the expression of catalase, GSH peroxidase and superoxide dismutase (SOD) [ 281 ].…”
Section: Possible Effects Of Natural Bioactive Compounds In Metabomentioning
confidence: 99%